Diagnosis and treatment of pneumocystis pneumonia - a review article - Fadelelmoula, Tarig Eltoum Yagoub (Edelweiss Applied Science and Technology, 2024)
This study aims to comprehensively evaluate the literature on recent advances in the diagnosis and treatment of Pneumocystis Pneumonia (PCP). A thorough review of relevant literature was conducted. Data were sourced from electronic databases such as PubMed, Scopus, Google Scholar, and Medline, focusing on articles published within the last ten years. The review included 41 articles. The diagnosis of PCP has evolved with the development of molecular techniques, advanced imaging modalities, and artificial intelligence models. Trimethoprim-sulfamethoxazole (TMP-SMX) remains the mainstay of treatment. Corticosteroid adjunctive therapy (CAT) has demonstrated efficacy in improving outcomes, while emerging research suggests a potential role for immunomodulatory agents. Chemoprophylaxis with TMP-SMX remains the main stay of prevention in populations at risk. Despite advances in diagnostic technologies, treatment options for PCP have largely remained unchanged. There are currently no vaccines, and chemoprophylaxis remains the mainstay of prevention. Practical Immediate treatment is essential. New ELISA techniques are viable, while real-time PCR proves superior to nested PCR. Clinical judgment plays a critical role in supporting laboratory diagnoses. High-resolution CT scans may be warranted for evaluating immunosuppressed patients with suspected pneumonia when chest X-rays appear normal. Radiomics can assist in distinguishing PCP from other types of pneumonia in non-HIV patients. Trimethoprim-sulfamethoxazole remains the preferred treatment, with alternative options including dapsone with trimethoprim, clindamycin with primaquine, atovaquone, or pentamidine. Corticosteroid adjunct therapy (CAT) is beneficial in treating PCP, and chemoprophylaxis is essential for high-risk populations.